2013
DOI: 10.5047/eps.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of similar aftershocks of a large inland earthquake, the 2000 Western Tottori earthquake, in Japan

Abstract: We detected similar aftershocks of the 2000 Western Tottori earthquake and we have examined their spatial distribution on the source fault. Many similar aftershocks are distributed in the northern part of the source fault, but few in the southern part. Specifically, similar aftershocks on the source fault are located outside of the asperity. The cumulative slip estimated from the similar aftershocks is 0.4-2.4 cm. The largest one is found at the edge of the major asperity. We observe that shallower events show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…They also proposed an additional scaling of Δσ ∝ M 0 −1/4 between the static stress drop, Δσ, and the seismic moment for repeating earthquakes on a plate interface. However, a comparison between the slip of similar aftershocks of inland earthquakes and the aseismic slip from geodetic observations supports a general scaling of d ∝ M 0 1/3 (Hiramatsu et al 2011;Hayashi and Hiramatsu 2013). The estimated static stress drop in this study does not support the scaling of Δσ ∝ M 0 −1/4 (Fig.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…They also proposed an additional scaling of Δσ ∝ M 0 −1/4 between the static stress drop, Δσ, and the seismic moment for repeating earthquakes on a plate interface. However, a comparison between the slip of similar aftershocks of inland earthquakes and the aseismic slip from geodetic observations supports a general scaling of d ∝ M 0 1/3 (Hiramatsu et al 2011;Hayashi and Hiramatsu 2013). The estimated static stress drop in this study does not support the scaling of Δσ ∝ M 0 −1/4 (Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…This disagreement is possibly interpreted by a difference of seismic coupling between small asperities and the surrounding aseismic slip if a constant stress drop applies to repeating earthquakes on the plate interface (Hayashi and Hiramatsu 2013). A 100 % seismic coupling with a constant static stress drop provides d ∝ M 0 1/3 or T r ∝ M 0 1/3 , where T r is a recurrence time for repeating earthquakes.…”
Section: Discussionmentioning
confidence: 99%
“…All the large slip patches are predominately free of aftershocks. This trend agrees with the common observation that aftershocks are preferentially located in low‐slip regions of the fault [ Mendoza and Hartzell , ; Das and Henry , ; Woessner et al ., ; Hayashi and Hiramatsu , ]. Synthetic waveforms are compared with the data records in the supporting information (Figure S1).…”
Section: Source Analysismentioning
confidence: 99%
“…For tectonic earthquakes, Hiramatsu et al [] and Hayashi and Hiramatsu [] reported repeating earthquakes for which the NJ formula overestimates the background creep, similarly to the present case of Zebra repeaters. Those repeaters occurred in the aftershock sequences of two intraplate earthquakes, the 2007 Noto Hanto earthquake and the 2000 Western Tottori earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, repeaters not following the NJ formula have been reported, though cases are few. Hiramatsu et al [] and Hayashi and Hiramatsu [] found repeaters among aftershocks of large intraplate earthquakes that were likely induced by afterslip. They suggested that the amount of the background creep estimated from the simple sum of coseismic slips, which was much less than calculated from the NJ formula, was likely more appropriate.…”
Section: Introductionmentioning
confidence: 99%